Wittgenstein and Psychoanalysis: The Speaking Lion - Mladen Dolar (EJP import test, 2014)
Summary: Philosophical Investigations are centrally concerned with what could be termed, in psychoanalytic theory, the status of the ‘big Other’, namely the status of rules, the necessity to assume them combined with the impossibility to provide them with sufficient foundation, the absence of any meta-rule to rule the rules of language games. The Other is both presupposed and lacking, rules are neither uniform nor univocal nor universal. The problem of private language raises the problem of something that would escape the rule, and the paper is concerned with the question whether it can be mapped on the problem of the Freudian unconscious. The psychoanalytic interpretation hinges precisely on establishing a rule where there doesn’t seem to be any. The assumption of psychoanalysis is that the unconscious is the speaking lion that can be understood, but this puts into question both the notion of understanding and the notion of the Other. The paper argues for a conception of the unconscious as the break of the rule that cannot be recuperated or integrated into the universe of meaning.
Keywords: Wittgenstein; Psychoanalysis; the Unconscious; language games; Philosophical Investigations